Caracterización morfológica de alfalfa granada mejorada (Medicago sativa) inducida mediante rayos gamma en la alimentación animal - Aguilera Sipion, Alison Melina (2025)
Over the years, the demand for forage has significantly increased due to the constant growth of livestock farming in various regions around the world. In response to this need, many farmers, even since ancient times, have chosen alfalfa (Medicago sativa) as a highly nutritious feed source, thanks to its richness in proteins, vitamins, and essential minerals for animal development. However, like any plant species, alfalfa has certain limitations in its adaptability to different climatic and soil conditions, particularly in tropical areas. To address this issue, the Technical University of Babahoyo (UTB), committed to sustainable agricultural and livestock development, decided to fund the project titled “Variability of alfalfa (Medicago sativa) under tropical conditions through induced mutagenesis.” This study aimed to improve the morphological and genotypic characteristics of the Granada variety of alfalfa through the application of induced mutagenesis using a gamma ray irradiator. To achieve this, different irradiation doses (referred to as GY) were applied, using a completely randomized design with 6 treatments and 3 replications per treatment. The doses applied were: T1 = 0 GY (control), T2 = 100 GY, T3 = 150 GY, T4 = 200 GY, T5 = 250 GY, and T6 = 300 GY. The results showed that the 100 GY treatment led to significant improvements in stem diameter and seed germination rate, suggesting that this technique can be effective for optimizing alfalfa performance under tropical conditions such as those found in Ecuador’s coastal region.